Learning english as a competitive strategy for a professional in the tourism and hospitality industry an experience of cultural exchange this project is a final requirement in order to get a degree as a Professional of Administration for Tourism and Hospitality - Cucanchón Rodríguez, Eliana Yisel (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (99 páginas) : ilustraciones color.